Stable silicon isotopes of groundwater, feldspars, and clay coatings in the Navajo Sandstone aquifer, Black Mesa, Arizona, USA - Georg, R; Zhu, C; Reynolds, B; Halliday, A (2009)
We present some of the first analyses of the stable isotopic composition of dissolved silicon (Si) in groundwater. The groundwater samples were from the Navajo Sandstone aquifer at Black Mesa, Arizona, USA, and the Si isotope composition of detrital feldspars and secondary clay coatings in the aquifer were also analyzed. Silicon isotope compositions were measured using high-resolution multi-collector inductively coupled mass spectrometry (HR-MC-ICP-MS) (Nu1700 and NuPlasma HR). The quartz dominated bulk rock and feldspar separates have similar δ 30Si of -0.09 ± 0.04‰ and -0.15 ± 0.04‰ (±95% SEM), respectively, and clay separates are isotopically lighter by up to 0.4‰ compared to the feldspars. From isotopic mass-balance considerations, co-existing aqueous fluids should have δ 30Si values heavier than the primary silicates. Positive δ 30Si values were only found in the shallow aquifer, where Si isotopes are most likely fractionated during the dissolution of feldspars and subsequent formation of clay minerals. However, δ 30Si decreases along the flow path from 0.56‰ to -1.42‰, representing the most negative dissolved Si isotope composition so far found for natural waters. We speculate that the enrichment in 28Si is due to dissolution of partly secondary clay minerals and low-temperature silcretes in the Navajo Sandstone. The discovery of the large range and systematic shifts of δ 30Si values along a groundwater flow path illustrates the potential utility of stable Si isotopes for deciphering the Si cycling in sedimentary basins, tracing fluid flow, and evaluating global Si cycle. © 2009 Elsevier Ltd. All rights reserved.